Enterprise learning in action : education and economic renewal for the twenty-first century - Shuttleworth, Dale E. (Dale Edwin), 1938- (Educational management series., 1993)
Drawing on case studies in community and enterprise learning from around the world, Dale Shuttleworth shows how young people can be taught the enterprise skills which will enable them to survive in today's uncertain world.